2021
DOI: 10.3390/nu13061784
|View full text |Cite
|
Sign up to set email alerts
|

Black Cumin (Nigella sativa L.): A Comprehensive Review on Phytochemistry, Health Benefits, Molecular Pharmacology, and Safety

Abstract: Mounting evidence support the potential benefits of functional foods or nutraceuticals for human health and diseases. Black cumin (Nigella sativa L.), a highly valued nutraceutical herb with a wide array of health benefits, has attracted growing interest from health-conscious individuals, the scientific community, and pharmaceutical industries. The pleiotropic pharmacological effects of black cumin, and its main bioactive component thymoquinone (TQ), have been manifested by their ability to attenuate oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
159
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 306 publications
(322 reference statements)
1
159
0
3
Order By: Relevance
“…To further investigate the findings of various research, Fu et al discovered that longan possessed a ferric reducing antioxidant power (FRAP) value of 8.61 ± 0.44 µmol Fe (II)/g and a total phenolic value of 5.88 ± 0.34 µmol Trolox/g. The study also revealed a strong interaction (R2 = 0.8416) among the FRAP value and total phenolic content [59,64]. Several crops of longan have been studied for their antioxidant potential, and the cellular antioxidant activity (CAA) scores ranged from 0.49 to 6.71 mol quercetin equivalents (QE)/100 g of fruit with an average value of 2.76 mol QE/100 g of fruit.…”
Section: Antiproliferative Antioxidant Activity and Anticancer Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…To further investigate the findings of various research, Fu et al discovered that longan possessed a ferric reducing antioxidant power (FRAP) value of 8.61 ± 0.44 µmol Fe (II)/g and a total phenolic value of 5.88 ± 0.34 µmol Trolox/g. The study also revealed a strong interaction (R2 = 0.8416) among the FRAP value and total phenolic content [59,64]. Several crops of longan have been studied for their antioxidant potential, and the cellular antioxidant activity (CAA) scores ranged from 0.49 to 6.71 mol quercetin equivalents (QE)/100 g of fruit with an average value of 2.76 mol QE/100 g of fruit.…”
Section: Antiproliferative Antioxidant Activity and Anticancer Activitymentioning
confidence: 97%
“…Antioxidants are the chemical substances that can improve shelf-life by delaying the oxidation process when incorporated into cellular components, namely, DNA/RNA, protein, and lipid molecules, which are one of the main reasons for foodstuff degradation during production and storage [58]. Accordingly, bioactive compounds, particularly from plant sources, have become more critical in recent years [59]. Many plant-derived bioactive compounds, and crude vegetable and fruit extracts were known to positively affect the free radicals in biological systems as significant antioxidant compounds [60,61].…”
Section: Antiproliferative Antioxidant Activity and Anticancer Activitymentioning
confidence: 99%
“…Thymoquinone (TQ), the main active component of black cumin seed and its oil, was shown to promote the function of different vital organs, including kidney function [10]. Mounting evidence shows that black cumin and TQ can alleviate kidney complications caused by various stress factors, namely chemotherapeutic agents, metabolic deficits, and environmental toxicants [11]. Evidence from the preclinical studies has shown that black cumin seed (in the form of powder, extracts, or oil) and TQ protect against kidney injuries induced by ischemia [12,13], cancer chemotherapeutic drugs (methotrexate and cisplatin) [14,15], analgesics (paracetamol, acetylsalicylic acid and aspirin) [16][17][18], heavy metal (arsenic and cadmium) [19,20], pesticide (piconazole and diazinon) [21,22], and other chemicals (carbon tetrachloride and sodium nitrite) [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence, athough limited, also suggests clinical improvements in CKD patients treated with black cumin [25][26][27]. Besides, black cumin was shown to be effective in modifying various risk factors for kidney disease such as hypertension, atherosclerosis, dyslipidemia, hyperglycemia, and diabetes [11]. The kidney-protective effects of black cumin are owing to its antioxidant, anti-inflammatory, immunomodulatory, antiapoptotic, and antifibrotic properties [11,28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation